2011
DOI: 10.18388/abp.2011_2291
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial recognition of thermal glycation products derived from porcine serum albumin with lactose.

Abstract: Recently, glyco-therapy is proposed to prevent the interaction of bacterial lectins with host ligands (glycoconjugates). This interaction represents the first step in infection. Neoglycans referred to as PSA-Lac (PSA-Glu (β1-4) Gal) were obtained by conjugation of porcine serum albumin (PSA) with lactose at 80 °C, 100 °C and 120 ºC. Characterization studies of the products showed that PSA could contain 1, 38 or 41 added lactoses, depending on the reaction temperature. These neoglycans were approximately 10 tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Albumin modified with lactose (BSA-Lac) was used as the polymer for the synthesis of lactosylated albumin microspheres [ 14 , 15 ]. Three formulations labeled as MS-Lac1, MS-Lac2 and MS-Lac3, obtained by water-in-oil emulsion at three concentrations of crosslinker were imaged by scanning electron microscopy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Albumin modified with lactose (BSA-Lac) was used as the polymer for the synthesis of lactosylated albumin microspheres [ 14 , 15 ]. Three formulations labeled as MS-Lac1, MS-Lac2 and MS-Lac3, obtained by water-in-oil emulsion at three concentrations of crosslinker were imaged by scanning electron microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…K88 strains of ETEC that cause diarrhea in pigs possess an adhesin essential for disease to occur [ 19 ]. Recent reports show that K88 adhesin targets specific receptors containing galactose exposed when using lactosylated albumin [ 13 , 14 ]. In this study, the formulation of stabilized microspheres, antibiotic carriers, using lactosylated albumin as encapsulation polymer, was examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This coupling reaction of protein with sugar produces neoglycans. Previous reports indicate that glycation is favored by temperatures above 60°C, alkaline pH, and influenced by moisture and reaction time (Ledesma-Osuna et al, 2009;Sarabia-Sainz et al, 2011). Other factors, such as water activity, intrinsic properties of protein and sugar, and the amino group-reducing sugar ratio, influence the yields and types of the Maillard reaction products.…”
Section: Characterization Of Bsa-lacmentioning
confidence: 98%
“…These bacteria are a perfect model to study the feasibility of glyco-nanomaterials in different processes in the field of medicine (Miura et al, 2016;Sattin & Bernardi, 2016). Previously, we reported that the modification of BSA with lactose (BSA-Lac) through thermal glycation promotes recognition of the bacterial adhesin (Sarabia-Sainz et al, 2011). In addition, the BSA-Lac microspheres were recognized by partially purified K88 adhesin of E. coli K88 (Sarabia-Sainz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%